2019
DOI: 10.1016/j.ekir.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Eculizumab Use for Kidney Transplantation in Patients With a Diagnosis of Atypical Hemolytic Uremic Syndrome

Abstract: Introduction Recurrence of atypical hemolytic uremic syndrome (aHUS) in renal allografts is common, leading to dialysis and graft failure. Pretransplant versus posttransplant initiation of eculizumab treatment in patients with aHUS has not been rigorously investigated. We hypothesized eculizumab pretransplant would reduce dialysis incidence posttransplant. Methods Of patients enrolled in the Global aHUS Registry ( n = 1549), 344 had ≥1 kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 35 publications
6
67
0
1
Order By: Relevance
“…29 Treatment with eculizumab before KTx may avoid this complication. 30 In our cohort, only three out of 11 recipients with aHUS received eculizumab, two of whom are currently disease free with a functioning…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…29 Treatment with eculizumab before KTx may avoid this complication. 30 In our cohort, only three out of 11 recipients with aHUS received eculizumab, two of whom are currently disease free with a functioning…”
Section: Discussionmentioning
confidence: 94%
“…21 Currently, its use in pediatric transplantation has been increasing regardless of the type of donor. [26][27][28][29][30][31][32][33] In univariate analysis, both in CAKUT and non-CAKUT glomerular patients, early and late AR were predictors of graft loss (Tables 6 and 7). However, in multivariate analysis, early AR in non-CAKUT glomerular and late AR in CAKUT patients were independently related to graft failure (Tables 6 and 7).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the proposed restrictive approach in aHUS in adult transplant patients or in adult candidates for KTx [57] is highly questionable due to controversial results, limited recovery after eculizumab resumption, and lack of alignment with expert recommendations [22][23][24]33]. New information from the Global aHUS Registry analyzing the outcome of 188 KTx patients with at least 1 year of followup after their most recent transplant demonstrated significantly better 2-year eGFR (70.2 ml/min/1.73m 2 ) in the subgroup of patients receiving eculizumab beginning at the time of transplantation in comparison with the subgroup receiving eculizumab after KTx with a previous diagnosis of aHUS (44.8 ml/min/1.73m 2 ) or the subgroup diagnosed with aHUS and treated after KTx (24.2 ml/ min/1.73m 2 ) [58].…”
Section: Discontinuation Of Eculizumab and Restrictive Usementioning
confidence: 95%
“…The use of eculizumab as a preemptive strategy in KT candidates with known aHUS is ongoing. Several studies have reported the clinical outcomes of KT recipients with ec-ulizumab prophylaxis [89][90][91]. The results showed that eculizumab prophylaxis at the time of KT markedly reduced the incidence of recurrent TMA events, compared to data from the era before eculizumab [28,86].…”
Section: Kidney Transplantationmentioning
confidence: 99%